Technology Entrepreneurship Project (ENT 600) : Senko 3 in 1 Multipurpose Sport Shoes / Aiman Haakim Nor Azhar - Nor Azhar, Aiman Haakim; Mazzelan, Muhammad Alifuddin; Azizan, Muhammad Adam Ikhwan; Mohd Tahir, Muhammad Nussair; Abdul Wahab, Muhammad Aizuddin (2021)
We are Senko Enterprise , and we work in the sports footwear industry. Senko Enterprise is a footwear business that provides a sport footwear which target to satisfy the demands of its customers. This company's management team is made up of five important partners: the General Manager, the Administration Manager, the Financial Manager, the Operation Manager, and the Marketing Manager. Each of the colleagues is responsible for carrying out useful items for consumers and also for managing this company. Besides that, in our company, we have released one sporting equipment which is Multipurpose Sport Shoes that employs cutting-edge technology to give consumers with comfort while wearing it. "Senko 3 in 1 Multipurpose Sport Shoes" is the name of our product. So, we produce this product in order to help athletes, universities and others that playing sports to reduce from buying different kind of shoes for kind of sports. With our product it can help give them playing sport using one shoes in 3 kinds of sports. We have set very low pricing in order to entice more people to utilise our products; the prices may be found within if you want to learn more. Because we appreciate our clients, we do not set excessive pricing because we want to establish a brand name that is widely recognised. This is due to the fact that high costs would delay purchases. In this blueprint shows regarding the flow for establish this products. Lastly, we also have set up project milestones in order to make the flow for opening our shop and establish our new products smoothly.